Effect of Fish Meal and Poultry Waste Meal on Vitamin Composition (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Fish meal is a valuable source of B-complex vitamins (riboflavin, niacin, pantothenic acid, choline, Vitamin B12) and fat-soluble vitamins (A and D). Poultry waste meal (PBM) can also contribute to the vitamin profile of feed, although it may not be as rich in certain vitamins compared to fish meal. Studies have shown that PBM can be a suitable alternative to fish meal